The baptistery of St Lydia in northern Greece - Katerina Seraïdari (Via@)
Constructed in 1974, the baptistery of St Lydia commemorates a founding event in Christian history: Lydia’s baptism by Paul in 49 or 50 AD in the river at Philippi. This article examines how this iconic baptism (considered to be the first on the European continent) was initially commemorated in the nineteenth century by Georgios Lampakis, a Greek scholar, who transformed water from Philippi into an artefact which was exhibited in an Athens museum. The construction of a church meant that something which could hitherto be moved between locations was monumentalized and embedded spatially; as a result of the international mobility generated by this baptistery, the area itself has been reclassified. This case study therefore provides a clearer understanding of interactions between the four principal parameters of religious tourism: the religious site, people, objects, and events.